„Forgotten queen” : Was the Jewish women Šīšīnduxt the mother of the Iranian šāhānšāh Wahrām V Gōr? - Maksymiuk, Katarzyna (Instytut Historyczny Uniwersytetu Wrocławskiego, 2019)
The origin of the mother of the Iranian šāhānšāh Wahrām V (420-438), son and successor of Yazdgird I (399-420), is, in scholar literature, treated marginally. The literary source which mentions Wahrām’s Jewish maternal background is the Šahrestānīhā ī Ērānšahr (‘The Provincial Capitals of Ērānšahr’). These considerations are an attempt to ‘recover the memory' of Šīšīnduxt, the Jewish women at the Iranian court, by methodical re-analyzing of the historical texts